PENGGUNAAN MULTIMEDIA INTERAKTIF DALAM MENINGKATKAN KEMAMPUAN MEMBACA PERMULAAN DI SEKOLAH DASAR - Sulistian Mudhiyyan Ningrum; Ahmad Nurefendi Fradana (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
Beginning reading is the first step to reading comprehension. Broughton states that there are two aspects of beginning reading, namely, mechanical skills and comprehension skills. Factors that can hinder beginning reading are internal factors and external factors. The purpose of this study was to determine the use of interactive multimedia in improving early reading skills in elementary schools. The research was conducted at SDN Lemahputro 1 in class 1 A with an experimental quantitative research method, the research design was One Group Pretest Posttest Design. The data collection techniques in this study were observation and tests. Assessment is carried out with observation sheets or observations and tests in the form of Pretest Posttest. Analysis of the paired sample T-test using SPSS 26 obtained the results of the Sig value. (2-tailed) 0.001 <0.05 then Ho is rejected and Ha is accepted. The average before treatment was 71.70 and after treatment it was 82.10. It can be concluded that there is an influence in the use of interactive multimedia to improve early reading skills.